Therapeutic Effects of Cold Atmospheric Plasma on Solid Tumor - Min, Tianhao; Xie, Xin; Ren, Kaijie; Sun, Tuanhe; Wang, Haonan; Dang, Chengxue; Zhang, Hao (Frontiers in Medicine, 2022)
Cancer is a devastating disease, and there is no particularly effective treatment at present. Recently, a new treatment, cold atmospheric plasma (CAP), has been proposed. At present, CAP is confirmed to have selective killing effect on tumor by many studies in vitro and in vivo. A targeted literature search was carried out on the study of cold atmospheric plasma. Through analysis and screening, a narrative review approach was selected to describe therapeutic effects of cold atmospheric plasma on solid tumor. According to the recent studies on plasma, some hypothetical therapeutic schemes of CAP are proposed in this paper. The killing mechanism of CAP on solid tumor is expounded in terms of the selectivity of CAP to tumor, the effects of CAP on cells, tumor microenvironment (TME) and immune system. CAP has many effects on solid tumors, and these effects are dose-dependent. The effects of optimal doses of CAP on solid tumors include killing tumor cells, inhibiting non-malignant cells and ECM in TME, affecting the communication between tumor cells, and inducing immunogenic death of tumor cells. In addition, several promising research directions of CAP are proposed in this review, which provide guidance for future research.